2019
DOI: 10.1155/2019/5362795
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structure, and Properties of Modified Asphalt with Waste Packaging Polypropylene and Organic Rectorite

Abstract: The modified asphalt with waste packaging polypropylene (WPP) and WPP/organic rectorite (OREC) was prepared by the melt blending method. The effects of OREC on the physical and aging properties of WPP-modified asphalt were studied. The morphologies, microstructure, and thermal properties of WPP-modified asphalt and WPP/OREC-modified asphalt were characterized by fluorescence microscopy, Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermogravimetry (TG). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that the addition of waste PVC increases the viscosity and stiffness of base asphalt so that the modified asphalt has better rutting resistance. One possible reason is that the chloride and carbon bond dipole in PVC provides a greater stiffness [ 73 ]. A study by Ziari [ 74 ] indicated that waste PVC improves the fatigue resistance, but the thermal cracking resistance is poor.…”
Section: The Use Of Waste Plastics In Asphaltmentioning
confidence: 99%
“…Recent studies have shown that the addition of waste PVC increases the viscosity and stiffness of base asphalt so that the modified asphalt has better rutting resistance. One possible reason is that the chloride and carbon bond dipole in PVC provides a greater stiffness [ 73 ]. A study by Ziari [ 74 ] indicated that waste PVC improves the fatigue resistance, but the thermal cracking resistance is poor.…”
Section: The Use Of Waste Plastics In Asphaltmentioning
confidence: 99%
“…Chen et al developed a modified asphalt using waste packaging PP and organic rectorite (OR). The modified asphalt contains 4 wt% PP and 1.5 wt% OR demonstrating good ductility and plasticity [6]. In addition, PP enhanced the indirect tensile strength, Marshall stability, and deformation resistance of asphalt mixes [4,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, several waste materials have been employed to enhance the properties of bitumen and asphalt mixtures [4,5]. Those materials include sulphur [6], mineral acids [7] and waxes [8], but the most employed waste materials are the plastics (i.e., polymers) [9,10], which include: Polyethylene Terephthalate (PET) [11], High density polyethylene (HDPE) [12,13], Low Density Polyethylene (LDPE) [14], Polystyrene (PS) [15], Polyurethane (PU) [16,17], Polypropylene (PP) [18], acrylonitrile butadiene styrene (ABS) [19], polyvinyl chloride (PVC) [20][21][22] and ethylene vinyl acetate (EVA) [23,24]. Some of these materials are usually used as bitumen modifiers, whose beneficial performance effects are highlighted in comparison with traditional bitumen and commercial modified bitumen [25,26].…”
Section: Introductionmentioning
confidence: 99%